Current status of the threatened Olrog's Gull Larus atlanticus: global population, breeding distribution and threats - Yorio, Pablo (2013)
Olrog's Gull Larus atlanticus breeds only in Argentina and is currently categorized as Vulnerable. Knowledge of the location of colonies and an updated understanding of human activities that may impact their breeding populations are crucial to the development of adequate conservation and management actions. In this paper we update the breeding distribution and abundance of Olrog's Gull, using information from three aerial surveys (2004, 2007 and 2009) in its main breeding area, Buenos Aires Province, complemented by additional nest counts in southern Chubut Province, covering its entire breeding range. We also provide an updated and more detailed account of threats faced by Olrog's Gulls at their nesting grounds, and summarise progress made towards their protection. The number of breeding sites was 7-12 per year, with locations differing among years. Five previously unrecorded breeding locations were identified. Colony size ranged from 5 to 3,540 breeding pairs, with the total breeding population 4,860-7,790 pairs, 98% of which nest in southern Buenos Aires Province. The main threats faced by breeding Olrog's Gulls include coastal development, pollution, sport fishing and unregulated tourism and recreational activities. Recent strengthening of the protected area system in Argentina has resulted in all known breeding sites, with the exception of Isla Brightman, falling within protected areas. We need comprehensive, simultaneous surveys to track global population trends. Despite enhanced protection of Olrog's Gull breeding populations, efforts are still needed to ensure that guidelines for their protection are included in management plans and that these are implemented effectively.